Susan B. Anthony papers - Anthony, Susan B. (Susan Brownell), 1820-1906.; Anthony, Mary S.
Correspondence, diaries, daybook, speeches, scrapbooks, and miscellaneous papers relating primarily to Anthony's writings, lectures, and other efforts on behalf of women's suffrage and women's rights. Includes material pertaining to the National Woman Suffrage Association, after 1890 the National American Woman Suffrage Association, and to the New York State Woman Suffrage Association. Other topics include abolition and the American Anti-Slavery Society, African American suffrage, Abraham Lincoln's assassination, temperance, and education of women. Individuals represented by either correspondence or diary entries include Rachel Foster Avery, Amelia Jenks Bloomer, Adelaide Johnson, Lucretia Mott, Wendell Phillips, Parker Pillsbury, Anna Howard Shaw, Elizabeth Cady Stanton, and Lucy Stone. Also includes material by and relating to Anthony's sister, Mary S. Anthony.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Library of Congress Rare Book and Special Collections Division.
Reformer and suffragist.
Collection material in English.
Keywords: Avery, Rachel Foster, -- 1858-1919.; Bloomer, Amelia Jenks, -- 1818-1894.; Johnson, Adelaide, -- 1859-1955.; Lincoln, Abraham, -- 1809-1865 -- Assassination; Mott, Lucretia, -- 1793-1880.; Phillips, Wendell, -- 1811-1884.; Pillsbury, Parker, -- 1809-1898.; Shaw, Anna Howard, -- 1847-1919.; Stanton, Elizabeth Cady, -- 1815-1902.; Stone, Lucy, -- 1818-1893.; American Anti-Slavery Society; National American Woman Suffrage Association; National Woman Suffrage Association (U.S.); New York State Woman Suffrage Association; African Americans -- Suffrage; Antislavery movements; Slavery; Social problems; Temperance; Women -- Education; Women -- Suffrage; Women's rights; Reformers; Suffragists